تطبيق إدارة الجودة الشاملة في برنامج تعليم اللغة العربية بجامعة الراية - Taqyuddin Ibnu Syafi’i CM; Nuril Mufidah; Abdul Malik Karim Amrullah; Muhammad Furqon Almurni (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Abstract This research on the implementation of Total Quality management was conducted at STIBA Ar Raayah and focused on the elements of teamwork, customer focus, and employee involvement and empowerment. This research uses qualitative research descriptive method. Data obtained from document research and interviews with the Director of STIBA Ar Raayah and ten students. The results obtained show that STIBA Ar Raayah applies the TQM concept in improving the quality of education offered. This is characterized by good cooperation in the application of communication with Arabic between lecturers and students, good response from students namely an increase in speaking skills in Arabic in a language environment, proud achievements in Arabic language competitions at national and international levels, and employees feel involved in decision making in the form of regular meetings between lecturers and student activities.